Respuesta :

Space

Answer:

γ = [tex]\lim_{n \to \infty}\sum_{k=1}^n (\frac{1}{k}-ln(n) )[/tex]

or

γ = -∞

Step-by-step explanation:

Let's solve what's inside the limit first.

We see that we need to take the sum of the entire thing. Since it is multivariable and we are given 1 variable, it stays the same.

Now we move on to the limit.

We replace n in the summative with infinity.

The natural log of infinity is infinity.

1 minus infinity would be negative infinity.

The sum of negative infinity of k = 1 is negative infinity.

So the limit as n approaches infinity would be negative infinity.

If we were to simplify this mathematically, it would just be the same equation.